Increased risk of dementia among people with a history of fractures: a systematic review and meta-analysis of population-based studies - Su, Li; Liao, Youyou; Liu, Xueqiao; Xie, Xin; Li, Yujie (Frontiers in Neurology, 2023)
Abstract Background: Emerging evidence suggests that there may be an association between history of fractures and dementia risk, but the epidemiological findings are inconsistent. We therefore conducted a meta-analysis to systematically assess the risk of dementia among people with history of fractures. Methods: We comprehensively searched four electronic databases (PubMed, Web of Science, Embase, and Cochrane Library) for relevant literature published from inception to January 10, 2023. Longitudinal observational studies that investigated the association between any type of fracture occurrence and subsequent risk of dementia were included for qualitative and quantitative analysis. Risk estimates were pooled using fixed-effects or random-effects models according to the level of heterogeneity. The Newcastle-Ottawa scale was used to evaluate the risk of bias in included studies. Results: Seven population-based studies involving 3,658,108 participants (136,179 with history of fractures) were eventually included. Pooled results showed a significant association between fracture and subsequent risk of dementia (hazard ratio [HR] = 1.28, 95% confidence interval [CI]: 1.11-1.48) in cohort studies. Patients with fractures at different sites showed a similar trend towards increased risk of subsequent dementia. No gender, age, region, duration of follow-up, study quality, or study design specificity was observed. Sensitivity analysis indicates that the current results were robust. No publication bias existed. The results were similar in the cohort study with the standardized incidence ratio (SIR) as the statistical measure (SIR = 1.58, 95% CI: 1.25-2.00) and in the case-control study (OR = 1.38, 95% CI: 1.18-1.61). Of note, the causal relationship between fracture and dementia was not demonstrated in this meta-analysis. Conclusions: People with history of fractures are at increased risk of developing dementia. Enhanced screening and preventive management of dementia in people with history of fractures may be beneficial.